Association of Teenage Pregnancy with Increased Risk of Maternal and Neonatal Complications: An Overview - Paller L; Feldman F; Lauria W; Rey G (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
The present study examines whether teenage pregnancy is associated with an increased risk of maternal and neonatal complications compared to adults through a systematic literature review to help clinicians in their actions before and during pregnancy in adolescents. Adolescent pregnancy is still a common occurrence, mostly in developing nations. Because it is associated with both obstetric and perinatal outcomes, maternal age is an important factor to consider while managing obstetric patients. A literature review to address the obstetric results of pregnancy in teenage mothers was conducted. Articles for the last 5 years in different databases including ‘Pregnancy’, ‘Teenager’, ‘Adolescent’, ‘Complications’, and ‘Outcomes’ as keywords were reviewed. A total of 2260 articles were obtained after the initial search, but only 28 met the inclusion criteria and were therefore reviewed. The outcomes were divided into complications of pregnancy, childbirth, puerperium, and neonatal complications. It was found that there is an association between young maternal age and preterm birth, pre-eclampsia/eclampsia, fetal growth restriction, and stillbirth, among others. The results of this review indicate that there is an association between young maternal age and low birth weight, preterm birth, pre-eclampsia/eclampsia, anaemia, fetal growth restriction, stillbirth, and premature rupture of membranes. For the newborn, it was found that outcomes such as low APGAR scores and admission to intensive care were more frequent in teenage mothers. It is assumed that the risk is greater when taking into account other aspects such as the socio-economic and cultural impact on adolescents or the weight of parenting, data that do not arise from our research but should be the object of further studies. Finally, it is recommended that future research addressing adolescent pregnancy could help better understand this phenomenon and its implications.